2004
DOI: 10.1532/ijh97.na0402
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Demonstration of Clonal Chromosome Abnormalities and Apoptosis in Individual Marrow Cells in Myelodysplastic Syndrome

Abstract: Bone marrow samples from 18 patients with myelodysplastic syndrome (MDS) with clonal cytogenetic abnormalities were characterized by combining fluorescence in situ hybridization (FISH) with in situ end-labeling (ISEL) or with annexin V staining and flow cytometry (AV/FLOW) to determine the clonal nature of hematopoietic cells undergoing apoptosis in marrow cells. Apoptosis occurred in both normal and clonal cells. However, the proportion of clonal cells identified by FISH among apoptotic cells was lower than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…Pearson's linear regression haematologica | 2013; 98(3) . Cells were co-cultured with HS5 stroma as described 18 …”
Section: Discussionmentioning
confidence: 99%
“…Pearson's linear regression haematologica | 2013; 98(3) . Cells were co-cultured with HS5 stroma as described 18 …”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] MDS has been considered a cell-autonomous disorder, and various mutations in hematopoietic cells have been described; however, recent data indicate that, in addition, cellular and noncellular components of the marrow microenvironment are involved in the pathophysiology of MDS and contribute to the broad spectrum of clinical presentations. [5][6][7] We and others have shown that, particularly in early stage/low-grade MDS, apoptosis occurs in both residual normal (polyclonal) and clonal hematopoietic precursors, 8,9 albeit at a consistently lower rate in clonal cells. 8 This lower apoptotic rate is associated with a survival advantage of the clone.…”
Section: Introductionmentioning
confidence: 94%
“…[5][6][7] We and others have shown that, particularly in early stage/low-grade MDS, apoptosis occurs in both residual normal (polyclonal) and clonal hematopoietic precursors, 8,9 albeit at a consistently lower rate in clonal cells. 8 This lower apoptotic rate is associated with a survival advantage of the clone. With more advanced MDS, clonal hematopoietic precursors become increasingly resistant to proapoptotic signals 8 and in a proportion of patients MDS will evolve to acute myeloid leukemia (AML).…”
Section: Introductionmentioning
confidence: 94%
“…Whereas patients with MPD show proliferative characteristics in the bone marrow, apoptosis is prominent in patients with MDS. Cytokines such as TNF␣, and the proapoptotic Fas-ligand and TNF-related apoptosisinducing ligand (TRAIL), are up-regulated in patients with MDS (3), and the neutralization of TNF␣ (4-6), for example with the soluble TNF receptor etanercept (7), enhances hematopoiesis in vitro and in vivo (6,8,9). TNF␣ is of particular interest because, in addition to proinflammatory activity, it provides both proapoptotic and proliferative signals (9).…”
mentioning
confidence: 99%
“…TNF␣ is of particular interest because, in addition to proinflammatory activity, it provides both proapoptotic and proliferative signals (9). In early stage MDS, apoptosis occurs in both residual normal and clonal hematopoietic precursors (8). The rate of apoptosis in clonal precursors declines as the disease progresses.…”
mentioning
confidence: 99%